Isolation and virtual screening of antimicrobial prodigiosin pigment from oxalotrophic Serratia marcescens OX_R strain - Mangesh V. Suryavanshi, Samadhan R. Waghmode, Nidhi Bharti, Prafulla B. Choudhari, Tejashri B. Hingamire, Yogesh S. Shouche (Journal of Applied Pharmaceutical Science, 2016)
Prodigiosin a multifaceted secondary metabolite produced by Serratia spp. having great potential as a pharmaceutical. In the present study we demonstrate that oxalate supplementation in peptone glycerol production media increased organoleptic characters and yield of prodigiosin pigment extracted from oxalotrophic Serratia marcescens OX_R isolated from Indian bat guano sample. The pigment was demonstrated in-vitro as an antibacterial agent against common opportunistic skin surface pathogen Staphylococcus aureus NCIM 5021 strain as killing activity by agar well diffusion method. The docking analysis and pharmacophore modelling indicated that the probable mechanism of action of the prodigiosin was against Staphylococcus aureus DNA gyrase protein. The pigment was also found to efficiently dye both cotton and latex polymer. In summary, we describe here an oxalotrophic Serratia marcescens which may serve as a potent and economical resource of prodigiosin which owing to its dyeing and anti-bacterial activities finds future avenues to be developed as dressing material for nosocomial subjects or burn victim patients.
Keywords: Oxalotrophic, Serratia marcescens, prodigiosin, natural dyeing agent.